National security and arms control in the age of biotechnology the Biological and Toxin Weapons Convention - Gerstein, Daniel M. 1958- (Rowman & Littlefield Publishers, Inc., 2013)
This book accessibly and expertly details the history and implications of the BWC - the Biological and Toxin Weapons Convention - a controversial arms control agreement drafted in the 1970's meant to supplement the Geneva protocol for warfare from decades earlier. That treaty banned the use of biological weapons in modern warfare, but failed to ban their development, transport or trafficking, holes the BWC aimed to fill, but are still contested to this day. The author traces the origins of the treaty and its many complications, past and present, while prescribing a way for the world's leaders to move forward with regards to (what he sees will be and already is) "the most important arms control treaty of the 21st Century." This will only become more pronounced as exponential advances in biotechnology continue to occur. The strength and enforcement of the treaty are at a crossroads, and it is important for both professionals and students of the political-military and international affairs to know exactly what a failure to honor, improve and uphold the BWC would mean for international security